University Students' Resilience Level: The Effect of Gender and Faculty. (13th May 2015) - Erdogan, Emine; Ozdogan, Oznur; Erdogan, Mehmet
Abstract: This study aimed at revealing university students' psychological resilience level and its relation with some selected factors (gender and faculty). The participants consisted of 596 university students (216 males, 378 females and 2 no response) selected from various fields in the faculties of Education and Theology. Data was collected through using of "Resiliency Scale" (Gurgan, 2006) with eight sub-scales. Two factor ANOVA was run to examine the effects of gender and faculty on students' resilience level and also sub-scales of resilience. Students' resilience level was higher than average score (M = 187, SD = 30.57, Range = 50-250) Male students showed significantly higher resilience level than did female students [F (1, 590) = 10.053, p < 0.05]. Furthermore, the interaction effect of gender and faculty on resilience was also significant [F (1, 590) = 5.98, p < 0.05]. Male-female difference was significant for the sub-scales of "Being Powerful" [F (1, 590) = 10.16, p < 0.05], "Being Entrepreneur" [F (1, 590) = 16.25, p < 0.05], "Foresight"[F (1, 590) = 7.32, p < 0.05], "Achieving the goal" [F (1, 590) = 8.07, p < 0.05], "Being a leader" [F (1, 590) = 4.71, p < 0.05] and "Being a researcher" [F (1, 590) = 6.27, p < 0.05] in favor of male students. Faculty differences was only observed to be significant for the sub-scale of "Being a leader" [F (1, 590) = 5.12, p < 0.05] in favor of faculty of education. The implications of the study will be given during the presentation.